Ideas in trenches: Power and polemics in Panagiotis Kondylis - Λαθύρης Παναγιώτης (Public Realm. Postgraduate and Early Career Journal of Political Philosophy, 2025)
The author of the article attempts to examine the positions of Panagiotis Kondylis on the intellectual history and ideas’ polemical nature that is the basic feature for understanding the configuration and development of an idea-theory in history. In order to achieve a full understanding of the specific concept of the intellectual history, first of all we have to analyze the Greek thinker’s positions on the power and the way in which the search for power as a basic and irrevocable anthropological condition leads to a polemic condition within the social field. This polemic condition is also evident in the field of ideas, as ideas can be seen as the attempt to form worldviews by the respective subject or group of subjects that have the purpose of self-preservation and expanding their power. Therefore, in this article the emphasis is placed on two different areas of Kondylis’ thought, the philosophy of man and then on the description of the ideas’ formulation.